Peran Guru Pendidikan Agama Islam dalam Membina Akhlak Peserta Didik Autis - Utari, Lia; Kurniawan, Kurniawan; Fathurrochman, Irwan (JOEAI (Journal of Education and Instruction), 2020)
This study aims to find out how the role of teachers in instilling religious education to children with autism or children with special needs, education for children with special needs is not the same as other normal children's education here the role of the teacher is very important in conveying material to be given to students. This research is a type of library research using the approach of Islamic religious education. The results showed that the morals of students included a very important and major element in the process of Islamic education, in this case the role of Islamic religious education teachers was very important in shaping the character of autistic children so that they could play a role as a pointer, controller, directing the behavior and actions of students. Moral development must be supported with comprehensive Islamic knowledge, faith and at the same time true faith so that it can develop the basic potential of humans to be kind, think well and behave well. Conclusion, Islamic education teachers have an important role in directing and guiding the morals of autistic children, moral development in autistic children is also one step to educate autistic children so that they can develop according to their age. Keywords: Islamic Religious Education, Morals, Autistic Students